ANALISIS DETERMINAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN/KOTA PROVINSI MALUKU UTARA - Yohana Petronela D. Solapung; I Wayan Priyana Agus Sudharma (Jurnal Ekonomi dan Bisnis, 2026)
Community welfare is an important indicator that can be used to assess the success of regional development. The level of community welfare is influenced by various economic and social factors such as Gross Regional Domestic Product (GRDP), income disparity, unemployment, investment, and regional government capital expenditure. North Maluku Province is one of the regions that has experienced rapid economic development in recent years, particularly due to the increasing industrial activities and investment. However, the increase in economic activities does not necessarily reflect an equal improvement in community welfare across all regencies and municipalities. This study aims to analyze the effect of GRDP, income disparity, unemployment, investment, and capital expenditure on community welfare in the regencies and municipalities of North Maluku Province during the period 2019–2023. The analytical method used in this study is a quantitative analysis with a panel data approach using the Fixed Effect Model (FEM). The results show that simultaneously GRDP, income disparity, unemployment, investment, and capital expenditure have a significant effect on community welfare in the regencies and municipalities of North Maluku Province during the study period. Partially, GRDP and income disparity have a positive but insignificant effect on community welfare. Meanwhile, investment and capital expenditure have a positive and significant effect on community welfare, while unemployment has a negative and significant effect on community welfare in the regencies and municipalities of North Maluku Province. Based on these findings, local governments are expected to improve the quality of economic growth through the optimization of investment and more effective allocation of capital expenditure, as well as expanding employment opportunities in order to enhance community welfare more evenly.